Law Enforcement Against Pollution of Beef Cattle Livestock Waste - Fauzul Romansah (Administrative and Environmental Law Review, 2020)
The beef cattle business does not only have a positive impact in meeting food needs, especially the fulfillment of nutrition in the form of animal protein. But it also has a negative impact on the environment and people. This environmental impact is caused by housing factors, food factors, and disease prevention and control factors. The housing factor contributes to environmental pollution in the form of air pollution and water pollution. This research was conducted using a descriptive analysis approach which resulted in the conclusion that the factors that can affect environmental pollution from beef cattle fattening business, including management system factors whose management is not good, especially in the settlement of animal manure can cause unpleasant odors, water pollution, and pollution. soil. Meanwhile, the food factor has a very negative impact due to leftover feed and the expansion of fertile land for the production of food sources for cattle through deforestation which produces greenhouse gas effects. Manure management is needed to make it more environmentally friendly, as well as providing vaccines for livestock to prevent transmission of livestock diseases to humans.